A survey of vocabulary learning strategies among primary students in a selected school in FELDA settlement in Pahang - Nur Fadhila Ahmad; Tg. Nor Rizan Tg. Mohd. Maasum (Fakulti Sains Sosial dan Kemanusiaan, Universiti Kebangsaan Malaysia, 2018)
For an effective English learning process, learners have to be familiar with their way of learning. Strategies to learn vocabulary learning are essential in order for the learners to acquire new lexical items in English language. The aim of this paper is to describe English vocabulary learning strategies used by FELDA primary school students. The methodology used for the study is based on a quantitative approach. Thirty-six pre-UPSR students from a selected primary in one of the FELDA settlements in Pahang represent the study sample. A 25-items questionnaire adopted from Schmitt’s taxonomy for vocabulary learning strategies is used to collect data. Data is analysed using descriptive statistics. The mean score obtained shows that students from the selected settlements seldom applied vocabulary learning strategies. The highest frequency of strategies are Determination strategies while the lowest frequency strategies are Social (consolidation) strategies. The research findings could be regarded as useful guide for teachers in order to implement effective English Language teaching process and to raise learners’ awareness towards effective vocabulary learning strategies.